Molecular authentication of rapeseed in edible oils using double PCR systems - Kutateladze, Tamara; Bitskinashvili, Kakha; Vishnepolsky, Boris; Karchkhadze, Kakha; Datukishvili, Nelly (Journal of Food Technology Research, 2026)
Rapeseed (Brassica napus L.) is one of the world’s most important oilseeds, providing edible oil and protein-rich feed. Accurate identification of rapeseed is essential for food and feed authentication, traceability, and safety assessment. This study develops and validates new polymerase chain reaction (PCR) systems for the reliable and specific detection of rapeseed in seeds and processed oils. Primers targeting the rapeseed acetyl-CoA carboxylase (ACCase; BnACCg8) gene were designed, and PCR conditions were optimized following genomic DNA extraction from ground seeds and 700 µL aliquots of edible oils. DNA was isolated using two commercial kits, NucleoSpin Food and Olive Oil DNA Isolation, and PCR products were assessed by agarose gel electrophoresis. Uniplex PCRs demonstrated species specificity, producing 147-bp and 174-bp amplicons only in rapeseed DNA, with no amplification in soybean, sunflower, or maize. PCR bands from oils were weak or absent. Implementing a double-PCR approach increased detection sensitivity in oils by approximately fivefold. Strong, expected-size amplicons were obtained from all oil extracts, confirming reliable detection of rapeseed in both cold-pressed and refined varieties, regardless of extraction method. This approach offers a sensitive, rapeseed-specific molecular tool for verifying the botanical origin of edible oils. It is suitable for routine authenticity testing and quality control of rapeseed-based products, supporting regulatory compliance and reducing mislabeling risks within oil supply chains.